Suffering as divine discipline in the Old Testament and post-Biblical Judaism - Sanders, James A. (Wipf & Stock, 1955)
Lexical study of yasar in the Bible : scope and method -- Suffering as divine discipline in the life and message of Jeremiah -- Suffering as divine discipline in the Old Testament : scope and method -- Suffering as divine discipline in post-biblical Judaism : scope and method